Population Size Estimates for Men who Have Sex with Men and Persons who Inject Drugs - Oster, Alexandra M. (J Urban Health, 2015)
Understanding geographic variation in the numbers of men who have sex with men (MSM) and persons who inject drugs (PWID) is critical to targeting and scaling up HIV prevention programs, but population size estimates are not available at generalizable sub-national levels. We analyzed 1999–2010 National Health and Nutrition Examination Survey data on persons aged 18–59 years. We estimated weighted prevalence of recent (past 12 month) male-male sex and injection drug use by urbanicity (the degree to which a geographic area is urban) and US census region and calculated population sizes. Large metro areas (population ≥1,000,000) had higher prevalence of male-male sex (central areas, 4.4 % of men; fringe areas, 2.5 %) compared with medium/small metro areas (1.4 %) and nonmetro areas (1.1 %). Injection drug use did not vary by urbanicity and neither varied by census region. Three-quarters of MSM, but only half of PWID, resided in large metro areas. Two-thirds of MSM and two-thirds of PWID resided in the South and West. Efforts to reach MSM would benefit from being focused in large metro areas, while efforts to reach PWID should be delivered more broadly. These data allow for more effective allocation of funds for prevention programs.